The middle and the beginning of the late bronze age in the north-western Iberian peninsula - Bettencourt, Ana M. S. (2017)
The aim of this paper is to present a synthesis on the Middle Bronze Age and the origins of the Late Bronze Age in the Northwest of Iberia. This approach takes into account the burial contexts and practices and the new scenarios (compared to the Early Bronze Age) that structured the world and promoted social identities: settlements, some “natural spaces” and reinterpreted past loci. In many cases these “natural spaces” were sometimes materialized by the cere- monial deposition of metallic artefacts and the erection of statues-menhirs. New conceptions of the world, understandable in societies depending on husbandry, forestry and shepherding activi- ties, dedicated to the land, becoming more sedentary and bearing an animist cosmology increasingly connected to the properties of minerals, metallic artefacts and others elements, are also addressed.